Pengaruh Net Profit Margin, Current Ratio, Dan Debt To Equity Ratio Terhadap Pertumbuhan Laba Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - Rizki Rahmat Putra (CV. ITTC INDONESIA, 2024)
This study aims to analyze the effect of Net Profit Margin (NPM), Current Ratio (CR), and Debt to Equity Ratio (DER) on profit growth of companies listed on the Indonesia Stock Exchange (IDX) in the period 2019-2023. The study uses a quantitative method with a sample of 10 companies from a total population of 47 companies selected through purposive sampling techniques. Secondary data in the form of company financial reports were analyzed using multiple linear regression. The results of the study indicate that NPM, CR, and DER do not have a significant effect on profit growth in banking companies. Overall, the three independent variables do not have a significant effect on the dependent variable, namely profit growth. The analysis technique used is linear regression analysis with the SPSS version 25 application program.